2017
DOI: 10.3389/fpls.2017.01738
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Alternative Splicing Analyses Reveal Large Differences between Maize Lines B73 and Mo17 in Response to Aphid Rhopalosiphum padi Infestation

Abstract: Maize (Zea mays L.) is a staple crop worldwide with extensive genetic variations. Various insects attack maize plants causing large yield loss. Here, we investigated the responses of maize B73, a susceptible line, and Mo17, a resistant line, to the aphid Rhopalosiphum padi on metabolite and transcriptome levels. R. padi feeding had no effect on the levels of the defensive metabolites benzoxazinoids (Bxs) in either line, and Mo17 contained substantially greater levels of Bxs than did B73. Profiling of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 76 publications
1
33
1
Order By: Relevance
“…Preferentially, the path followed by the aphid's stylet to reach the phloem is intercellular and hence plant cell damage is minor. By contrast to findings with caterpillars, no changes in Bx-gene transcript levels were displayed in experiments with, e.g., Rhopalosiphum padi (Linnaeus, 1758) [157].…”
Section: Aphidscontrasting
confidence: 86%
“…Preferentially, the path followed by the aphid's stylet to reach the phloem is intercellular and hence plant cell damage is minor. By contrast to findings with caterpillars, no changes in Bx-gene transcript levels were displayed in experiments with, e.g., Rhopalosiphum padi (Linnaeus, 1758) [157].…”
Section: Aphidscontrasting
confidence: 86%
“…Caterpillar feeding‐ or wounding‐induced systemic signaling has been studied in several plant species, especially the solanaceous species tomato, tobacco ( Nicotiana tabacum ), and the brassicaceous species Arabidopsis ( Arabidopsis thaliana ) (Wu & Baldwin, ). Electrical signals, MAPKs and JA signaling are all involved in this process (Glauser et al ., ; Koo et al ., ; Mousavi et al ., ; Salvador‐Recatala et al ., ; Song et al ., ). Yet little is known about systemic signaling involved in plant defense against piercing–sucking insects.…”
Section: Introductionmentioning
confidence: 97%
“…Genetic variation in maize leads to variation in transcriptome and metabolite responses to pest attack. Song et al (2017) demonstrated that maize line B73 and Mo17 showed extensive differences in their responses in transcriptome and metabolite to Rhopalosiphum padi L. feeding. There is, therefore, an urgent need to study the transcriptomic and the metabolic responses of commercial maize to O. furnacalis attack at the mid-whorl stage, which could be of great practical significance in maize cultivation.…”
Section: Introductionmentioning
confidence: 99%